Unraveling the relationship between inflammation and cluster headache - Wang, Yu-Wen; Yang, Xu-Hong; Zheng, Xin-Hui; Zhou, Gao-Shui; Zhao, Xiao-Xia; Zhao, Yi-Lan; Wu, Shu-Hong (Frontiers in Neurology, 2025)
Cluster headache (CH) is often referred to as the ‘suicide headache.’ Existing research suggests that the activation of the trigeminal-vascular system, increased sensitivity of nerve fibers, and the release and interaction of various neuropeptides and inflammatory mediators may contribute to neurogenic inflammation, which serves as a crucial pathophysiological basis for the development of CH. Additionally, some neuropeptides can modulate neuronal activity related to pain transmission and may increase pain perception by sensitizing central nerves. This review discusses the neuropeptides and inflammatory mediators associated with CH neuroinflammation, focusing on calcitonin gene-related peptide (CGRP), inflammatory cytokines and related signaling pathways, nitric oxide (NO), pituitary adenylate cyclase-activating peptide 38 (PACAP-38), and vasoactive intestinal peptide (VIP), incorporating both preclinical and clinical evidence to provide new insights into potential therapeutic targets for CH.